Digital Transformasi: Hubungan Penerapan Industri 4.0 dalam Amalan Pengurusan Kualiti Menyeluruh Terhadap Prestasi Operasi Organisasi - Ahmad @ Mohamad, Md Fauzi; Lye Mei Ki; Ahmad Nur Aizat Ahmad; Abdul Latip, Hamrila (Research in Management of Technology and Business, 2022)
The aim of this research is to study the relationship between Total Quality Management (TQM) 4.0 and operation performance. Industry 4.0 had been used in several manufacturing sector to improve their business management. Therefore, this research focus on the adoption of industry 4.0 tools in total quality management, which are smart supervision, digital process control, smart supply chain, and real-time overall equipment effectiveness that impact on operation performance. This survey was answered by 130 respondents, who was working in manufacturing organization. The relationship between TQM 4.0 and operation performance was significant correlation. Thus, the adoption of industry 4.0 in TQM can improve manufacturing’s operation performance. It can help transfer their process flow become automation and digitalization.